Development of MISTION Software to Detect and Reduce Students' Misconception with Conceptual Change Text Strategy on Stoichiometry Materials - Rizky Amallia Prastika; Sukarmin Sukarmin (Journal of Educational Sciences, 2021)
Misconceptions often occur, especially in chemical material like stoichiometry which are full of abstract concepts. The purpose of this study was to determine the feasibility of mistion software to detect and reduce misconceptions in stoichiometric material with conceptual change text strategy. This research was conducted using the Research and Development (R&D) method with 15 students of SMAN 1 Gedangan as research subjects. Software is developed using Adobe Flash CS 6 with action script 3.0. The software's feasibility is viewed from the validity practicality, and effectiveness. The data analysis results show that 1) the software is very valid with the average result of content validation is 93.52%, and the construct validation is 91.82%. 2) The software is very practical, with an average result of student response questionnaires is 95.28% and supported with the average result of student observations is 85%. 3) Software is effective with the average result of misconception shift for sub-concept basic chemical law is 77.27% with effective category, sub-concept of reaction equation is 85.05% with very effective category, and sub-concept of mole is 73,72% with effective category. Based on the result, we can conclude that mistion software is feasible to detect and reduce students' misconception.